QUESTIONS AND PROBLEMS IN INTERACTION BETWEEN THE LABOUR MARKET AND THE MARKET OF EDUCATIONAL SERVICES - Konstantin G. Hrabrov (Статистика и экономика)
In the conditions of an accruing economic crisis the increasing relevance is gained by systems and the models optimizing a certain kind of activity. Considering an imbalance problem in training of specialists with the higher education, it is possible to note that there was no proper attention paid to modeling and optimization of strategy and tactics in the conditions of the competition on labor and employment markets. In this connection in present conditions the identification of the factors which are at the bottom of a mismatch of a labor market and the market of educational services is considered to be extremely important.